Stability of Traveling Wave Fronts for a Three Species Predator-Prey Model with Nonlocal Dispersals. (14th December 2019) - Yuan, Dongmei; Bai, Yuzhen
Abstract : In this paper, we consider a predator-prey model with nonlocal dispersals of two cooperative preys and one predator. We prove that the traveling wave fronts with the relatively large wave speed are exponentially stable as perturbation in some exponentially weighted spaces, when the difference between initial data and traveling wave fronts decay exponentially at negative infinity, but in other locations, the initial data can be very large. The adopted method is to use the weighted energy method and the squeezing technique with some new flavors to handle the nonlocal dispersals.